PROTEIN TOKSININSEKTISIDAL DARI BAKTERI PATOGEN SERANGGA Photorhabdus luminescens HJ - Alina Akhdiya; Etty Pratiwi; I Made Samudra (BERITA BIOLOGI, 2007)
Photorhabdus luminescens HJ is an entomopathogenic bacterium that has a high toxicity against Tenebrio molitor larvae.Toxicity assay of crude extra cellular protein precipitated using ammonium sulphate showed that the highest toxin activity was found in 70 % saturation. Purification of the toxin using Hi Prep 16/60 Sephacryl S-200 HR column exhibited one fraction of toxic protein and three fractions of non-toxic protein. Mortality of T. molitor larvae treated with 19.2 nanogram of toxic fraction was up to 80%. Denatured protein analysis using sodium dodecyl sulphate-polyacrylamide gel electrophoresis revealed that the toxic fraction was composed of three proteins, which were 19.5, 42, and 66 kDa respectively. Based on toxin activity bioassay, this toxin type was an injectable toxin and presumably classified as Mcf toxin.